Slang Words Analysis in The Movie Script "Inside Out 2" - Nayya Aulia Aisyah Pranyoto; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Slang has been widely used by various groups, especially teenagers, indicating that there is rapid development, increasingly advanced technology, and likewise, the entertainment media industry. This paper reports the results of a qualitative method that aims to explore and find data on the types of slang contained in the script of the movie Inside Out 2. According to Allan & Burridge's (2006) theory on the classification of slang word types, there are five types. The five types are Fresh & Creative, Clipping, Flippant, Acronym, and Imitative. By applying the five classifications to the Inside Out 2 movie script, there are a total of 229 data points, but only four types are found in the Inside Out 2 movie script, namely Fresh & Creative, Clipping, Flippant, and Imitative. Through the analysis of slang categories and their usage in the movie "Inside Out 2," this study aims to offer a valuable perspective on how the linguistic decisions of writers and filmmakers represent the speech patterns and life experiences of the younger generation.